Law and Ethics in Clinical Research - Palomo López, Patricia; Redondo Mena, Cristina (Revista Internacional de Ciencias Podológicas, 2012)
Clinical research is built on a series of hypotheses, from which we started working on patients (or animals), who may face serious risks or impacts. There was human research causing severe adverse effects for humanity, especially during wars and social conflicts. The most important date in this regard was the World War II, from which one could develop the Nuremberg Code, and thereafter, there are controls and laws, declarations and commissions, to minimize the risks of all people or animals involved in a scientific project.
Keywords: Nuremberg code; Helsinki declaration; informed consent.